Neglected tropical diseases and their control in Uganda - Kolaczinski, Jan H.; Onapa, Ambrose W.; Kabatereine, Narcis B. B.; Ndyomugyenyi, Richard; Kakembo, Abbas S. L.; Brooker, Simon (Malaria Consortium, 2006)
Neglected tropical diseases (NTDs) are a group of 13 infections caused by parasitic worms, protozoa or bacteria. They strike the world’s poorest people, living in remote and rural areas of low-income countries in Sub-Saharan Africa, Asia and the Americas, causing life-long disability, disfigurement, reduced economic productivity and social stigma. When expressed in disability-adjusted life years (DALYs), NTDs account for approximately one-quarter of the global disease burden from HIV/AIDS and for almost the same burden as malaria. For the first time, international advocacy is drawing attention to the global NTD burden and to the fact that substantial improvements can be readily achieved at relatively low cost. Targeting this group of diseases is therefore widely promoted as a means to reaching some of the Millennium Development Goals (MDGs). As many of the NTD occur in the same geographical areas and, in some cases, can be treated with the same drug, there is potential for integration of control activities, both within this group of diseases as well as with other interventions. Uganda is one of the Sub-Saharan countries affected by many NTDs, but also by HIV/AIDS, tuberculosis and malaria (‘the big three’). To date, most of the attention and funding has been dedicated to the control of ‘the big three’, though NTD specific efforts have been made and led to considerable achievements during implementation of the Health Sector Strategic Plan I (HSSPI) from 2000/01 to 2004/05.